HUBUNGAN TINGKAT STRESS DAN GAYA HIDUP TERHADAP KEJADIAN HIPERTENSI PADA LANSIA DI DESA KEMAMANG BALEN BOJONEGORO - Roni, Faishol; Bagus, Nanang; Fitriani, Eka Diah (LPPM STIKes Bahrul Ulum Jombang, 2018)
Entering old age is slow and progressive human will lose the resistance to infection so that the susceptible exposed degenerative diseases. Hypertension is one of the degenerative diseases that often occur. The hypertension is the disease that is called